POPULATION DYNAMICS OF AERO-ALGAL FLORA OF RURAL KANPUR - SUNITA VERMA; Z. H. KHAN (The Bioscan, 2012)
Ambient air environment of rural Kanpur was monitored during 2009-2010 to assess the population dynamics of the area. In all sixteen algal species were recorded. The most dominant group was Cyanophyceae. Among the genusOscillatoria was most prominent (10.9 % dominance) followed by Spirogyra (8.2% dominance).The least value was ofChlorococcum (4.1% dominance). The highest abundance of aero algae was recorded in April (62.5) the lowest algal count was observed in September (12.5) permutations in meteorological conditions affected the aero algal flora both quantitatively and qualitatively. The significance of aero algal flora observed has been discussed.